Physics of Quantum Rings (NanoScience and Technology,, 2018)
This book, now in its second edition, introduces readers to quantum rings as a special class of modern high-tech material structures at the nanoscale. It deals, in particular, with their formation by means of molecular beam epitaxy and droplet epitaxy of semiconductors, and their topology-driven electronic, optical and magnetic properties. A highly complex theoretical model is developed to adequately represent the specific features of quantum rings. The results presented here are intended to facilitate the development of low-cost high-performance electronic, spintronic, optoelectronic and information processing devices based on quantum rings. This second edition includes both new and significantly revised chapters. It provides extensive information on recent advances in the physics of quantum rings related to the spin-orbit interaction and spin dynamics (spin interference in Rashba rings, tunable exciton topology on type II InAs/GaAsSb quantum nanostructures), the electron-phonon interaction in ring-like structures, quantum interference manifestations in novel materials (graphene nanoribbons, MoS2), and the effects of electrical field and THz radiation on the optical properties of quantum rings. The new edition also shares insights into the properties of various novel architectures, including coupled quantum ring-quantum dot chains and concentric quantum rings, topologic states of light in self-assembled ring-like cavities, and optical and plasmon m.odes in Möbius-shaped resonators.